Towards Machine Translation for Security Surveillance (2021)
Global insecurity is one of the main challenges facing the world in recent times and Nigeria is among the most affected with thousands of deaths and loss of property worth billions of naira. Studies show that countries are achieving better security through the use intelligence reports where languages play significant roles than through the use of arms and ammunitions. However, previous studies on Nigerian languages have concentrated on language description and language documentation with little attention paid to language use for security surveillance and intelligence gathering This paper, therefore, evaluates Google translate, from the perspective of the Igbo and Yoruba languages. with a view to determining its level of efficiency in translating for the purpose of security surveillance or intelligence gathering, identifying its potentials for achieving better security and the challenges facing its use. The study reveals that Google translate could be used for security surveillance if properly adapted despite the shortcomings of its output. Factors such as multilingualism, inadequate funding, insufficient language resources and poor infrastructural development are some of the challenges facing the proposal. The implication is that the Nigerian government at all levels can harness the potentials of this tool towards overcoming its security challenges if it invests more in security especially at the State and Local Government levels.